PENGALAMAN MAHASISWA DALAM MENGAKSES FASILITAS KAMPUS: STUDI KASUS DI GEDUNG PPG UIN JAKARTA - Canggih Tri Satria -; Divani Truna Wijayanti; Nurazizah; Muhammad Rizki Fadhilah; Arif Saefudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The comfort, learning effectiveness, and general contentment of students within higher education contexts are greatly influenced by the availability and quality of campus amenities. In this study, we want to investigate how students at PPG UIN Jakarta have used and rated the campus amenities throughout their time here. Over the course of two months, this research used a case study strategy to gather qualitative data via in-depth interviews, field observations, and recording. Researchers and participants engaged in casual, open conversation to get information from students who were purposefully chosen to be informants and who made frequent use of university resources. To guarantee the correctness and trustworthiness of the results, data validity was reinforced by triangulation, member verification, and peer debriefing. Data analysis comprised reduction, presentation, and conclusion drafting. The main results indicate that although campus facilities are relatively comprehensive, students continue to encounter technical obstacles such as malfunctioning air conditioners, elevators, projectors, and unstable internet connectivity, which significantly diminish the quality of their user experience. The primary conclusion reveals that the effectiveness of facility management remains suboptimal due to weak preventive maintenance, slow responses to complaints, and improper user behavior in facility utilization. This study contributes to enriching the discourse on student experience–based facility management by emphasizing the need for responsive, transparent, and student-inclusive facility governance to enhance satisfaction, learning efficiency, and institutional quality.